2017
DOI: 10.4317/jced.53215
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestation and salivary changes in renal patients undergoing hemodialysis

Abstract: BackgroundSalivary changes in hemodialysis patients may result in various oral manifestations. This research intended to determine oral manifestations and some salivary markers in hemodialysis patients.Material and MethodsThis cross-sectional study was conducted on 30 hemodialysis patients (the patient group) and 30 healthy individuals (the control group). Saliva urea and calcium levels and pH values of the participants were measured, and oral manifestations such as pale mucosa, xerostomia, halitosis, changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
28
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 11 publications
6
28
0
13
Order By: Relevance
“…Oral symptoms such as xerostomia, dygeusia, halitosis and burning of the mouth [12,19] are frequently reported by the CKD patient. In the present study, the prevalence of dysgeusia was high, corroborating with the literature [6,11,12,[20][21][22].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Oral symptoms such as xerostomia, dygeusia, halitosis and burning of the mouth [12,19] are frequently reported by the CKD patient. In the present study, the prevalence of dysgeusia was high, corroborating with the literature [6,11,12,[20][21][22].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the average fluid intake was low (816.89 + 694.26 ml / day) and a high percentage of individuals with xerostomia was observed, a similar finding in some studies [6,8,12,20,21], however diferent from other authors' conclusions [14,19,22]. The divergence of results between studies may be due to the different characteristics of the samples, including the number and types of drugs consumed, mean age, reduction of salivary flow, average fluid consumption, among other characteristics of the individuals studied.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies have found reduced Ca levels in HD patients due to decreased levels of active vitamin D metabolites synthesized in the kidneys. The consequence is increased synthesis and secretion of the parathyroid hormone (secondary hyperparathyroidism), which causes low levels of Ca in the HD group [16]. The higher levels of Ca in PD patients may also be related to their higher dietary Ca intake and supplementation that they are recommended [17].…”
Section: Discussionmentioning
confidence: 99%
“…Patients on haemodialysis have higher salivary pH levels than do healthy controls. Moreover, haemodialysed patients have higher incidences of halitosis, xerostomia, calculus formation, and gum bleeding than healthy controls . The higher occurrence of gum bleeding in dialysed patients is a consequence of impaired haemostasis.…”
mentioning
confidence: 99%